Architecture Food Security as a Pillar of Sustainable Devel-opment in Perspective Maqashid Syariah : Approach System-atic Literature Review (SLR) (International Forum of Researchers and Lecturers, 2025)
This study examines the architecture of food security as a pillar of sustainable development from the perspective of Maqashid Syariah, using the Systematic Literature Review (SLR) approach. The issue of food security is crucial, considering its broad impact on social, economic, and political aspects, as seen from the significant surge in Indonesian rice imports in 2023 and 2024. Although Indonesia has great agricultural potential, challenges such as limited production capacity, inadequate distribution infrastructure, and undiversified consumption patterns remain obstacles. This study integrates the concepts of food security, sustainable development (SDGs), and Maqashid Syariah, which seeks to safeguard the five basic human needs: religion ( hifzh al-din ), life ( hifzh al-nafs ), reason ( hifzh al-aql ), offspring ( hifzh al-nasl ), and wealth ( hifzh al-mal ). By analyzing 16 relevant articles from databases such as Google Scholar and Scopus, this study synthesizes a conceptual framework that positions food security as a manifestation of hifzh al-nafs and hifzh al-mal , and sustainable development as a manifestation of universal maslahah . It is found that Maqasid Syariah provides not only ethical justification, but also an operational framework for building a resilient food security system and achieving holistic sustainable development, supported by government policies, the use of data technology, community participation, and Islamic financial instruments. This alignment confirms that food security and sustainable development are moral and spiritual imperatives in Islam, aimed at creating true welfare ( hayatan tayyibah ) for all people.